2019
DOI: 10.1155/2019/1750329
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of HER2 Amplification by Droplet Digital PCR in the Follow-Up of Gastric Cancer Patients Being Treated with Trastuzumab after Surgery

Abstract: Background. Circulating tumor DNA (ctDNA) derived from tumors is a promising biomarker for monitoring tumor status and evaluating therapeutic effects and prognosis. We studied the plasma human epidermal growth factor receptor 2 (HER2) amplification in gastric cancer (GC) patients by droplet digital PCR (ddPCR) during therapy with trastuzumab. Methods. A total of 12 patients were recruited after surgery. All patients received FOLFOX chemotherapy combined with trastuzumab as a treatment regimen. During the 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
(41 reference statements)
2
12
0
Order By: Relevance
“…This level of concordance between the results of the HER2 gene tests in cancer tissue and in liquid biopsy was also found in our study and in study by Kim et al [9]. In addition Kinuasa et al found that patients who had high number of HER2 gene copies in ct-DNA showed signi cantly shorter survival compared with HER2-negative patients [21]. The median HER2 gene copy number in ct-DNA in Kinugasa et al study was 1.15.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This level of concordance between the results of the HER2 gene tests in cancer tissue and in liquid biopsy was also found in our study and in study by Kim et al [9]. In addition Kinuasa et al found that patients who had high number of HER2 gene copies in ct-DNA showed signi cantly shorter survival compared with HER2-negative patients [21]. The median HER2 gene copy number in ct-DNA in Kinugasa et al study was 1.15.…”
Section: Discussionsupporting
confidence: 90%
“…Liu et al studied the plasma HER2 gene ampli cation in gastric cancer patients by droplet digital PCR (ddPCR) during 12 months of chemotherapy with uorouracil and oxaliplatin combined with trastuzumab [21]. They observed that the concordance rate of results of HER2 gene examination in plasma and FFPE tissue samples by ddPCR was 81.4%, with a sensitivity of 76% and a speci city of 84%.…”
Section: Discussionmentioning
confidence: 99%
“…Two research teams covered HER2 ddPCR with ctDNA, and one team measured HER2 ratio using ribonuclease P RNA component H1 (RPPH1) as a reference gene and the sensitivity and specificity of plasma HER2 ddPCR were 73.3% and 93.3%, respectively 22 . The other used elongation factor Tu GTP binding domain containing 2 (EFTUD2) as a reference gene and demonstrated the sensitivity and specificity were 76.5% and 83.8% 23 . Compared with the previous studies that measured HER2 ratios of gastric cancer patients using ddPCR [19][20][21][22][23][24] , our study covered the largest cohort to the best of our knowledge; moreover, we worked with paired samples of formalin-fixed and paraffin-embedded (FFPE) tissues and preoperative plasma cfDNA.…”
Section: Discussionmentioning
confidence: 99%
“…The other used elongation factor Tu GTP binding domain containing 2 (EFTUD2) as a reference gene and demonstrated the sensitivity and specificity were 76.5% and 83.8% 23 . Compared with the previous studies that measured HER2 ratios of gastric cancer patients using ddPCR [19][20][21][22][23][24] , our study covered the largest cohort to the best of our knowledge; moreover, we worked with paired samples of formalin-fixed and paraffin-embedded (FFPE) tissues and preoperative plasma cfDNA. We used EIF2C1 as the reference gene, and ddPCR using the HER2/EIF2C1 ratio demonstrated that it can assess HER2 status accurately 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation